Técnicos em farmácia: trajetórias formativas de egressos do curso técnico de nível médio em farmácia - Barros Neto, Sebastião Gonçalves de; Jacob, Alexandre (Revista Cocar, 2020)
Pharmacy technicians: formative trajectories of graduates of technical courses of vocational schools in pharmacy Resumo A pesquisa propõe-se analisar as trajetórias formativas dos Técnicos em Farmácia, egressos dos Cursos Técnicos de Nível Médio em Farmácia, pois, ao passo que se reconhece a Farmácia como promotora de saúde, entende-se que seus recursos humanos devem possuir educação formal específica, regulamentação ocupacional e profissional, registro e exercício profissional fiscalizado por órgão competente. Para concretizar a investigação, utilizou-se o estudo de campo descritivo de desenho —natureza qualitativa online (por intermédio da internet) —, com entrevistas assíncronas, realizadas por questionário semiestruturado enviado por e-mail para obtenção das histórias de vida (ou biografias). As narrativas das histórias formativas de vida dos profissionais de nível Técnico em Farmácia possibilitaram descrever, conhecer e problematizar o contexto da formação Técnica em Farmácia no Brasil e propor novos caminhos para a área Técnica em Farmácia Brasileira, em especial para a Educação Profissional e Tecnológica em Saúde. Palavras-chave: Técnico em Farmácia. Educação Profissional em Saúde. Políticas Públicas. Assistência Farmacêutica. Método (auto) biográfico. Abstract The research proposes the analysis of the formative trajectories of pharmacy technicians, graduates of technical courses of vocational schooling in Pharmacy. While recognizing this area as a promoter of health, it is understood that these professionals must have specific formal education, occupational and professional regulation, registration and professional exercise supervised by a competent body. To carry out the research, a descriptive qualitative field study was performed online (through the internet), with asynchronous interviews, carried out by a semi-structured questionnaire sent by email to obtain life histories (or autobiographies). These narratives of life histories of technical level professionals in Pharmacy allowed us to describe, know and problematize the context of their formation in Brazil and to propose new paths for the technical area in Brazilian Pharmacy, especially for professional and technological education in healthcare. Keywords: Pharmacy Technician. Professional Education in Health. Public Policies. Pharmaceutical Assistance. Autobiographical Method.